Faktor-Faktor Yang Mempengaruhi Ibu Dalam Pemberian Asi Berdasarkan Peran Ayah Dan Keluarga Di Desa Sigumpar Kecamatan Sigumpar Kabupaten Toba Tahun 2023 - Jane Wilda Irmawati Sirait (Jurnal Kesehatan, 2023)
Breast milk plays an important role in maintaining the health of newborns. Breastfeeding is a natural process in which the first 6 months of birth are expected to be full without additional food or what is known as exclusive breastfeeding, and continued breastfeeding until the child is 2 years old but supplemented with complementary foods. To be successful in breastfeeding, many factors are needed, including the role of the husband (father) and family. The research design used in this research is a descriptive research using a cross sectional approach which aims to determine the factors that influence mothers in breastfeeding in Sigumpar Village, Kec. Sigumpar, Toba Regency, 2023. The location of this research was in Sigumpar Village, Kec. Sigupar Kab. Toba. The reason for choosing Sigumpar Village was the success of all mothers who have babies 0-24 months in providing breast milk, which was taken from the data of midwives from Sigumpar Village, Kec. Sigupar Kab. Toba. The results of research and discussion of research on the factors that influence mothers in breastfeeding, namely: Demographic data on mothers who provide ASI aged 0-24 months based on work, the majority of respondents 40 people (71.4%) do not work, based on sources of information by workers health as many as 44 people (78.6%). From the factor of the father's role in supporting breastfeeding in mothers who have babies 0-24 months in the category of support as many as 56 people (100%). From the factor of the role of the family in supporting breastfeeding in mothers who have babies 0-24 months in the category of support as many as 56 people (100%).